2016
DOI: 10.1021/acsami.6b03310
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of SnO2 Asymmetric Membranes for High Performance Lithium Battery Anode

Abstract: Alloy electrode material like tin dioxide (SnO2) possesses much higher specific capacity as compared to commercial graphite anode in lithium ion battery (783 vs 372 mAh g(-1)). However, the huge volume change (260%) of SnO2-based anode during the alloying and dealloying process can cause significant electrode pulverization and rapid capacity loss. Herein we report the synthesis of SnO2 asymmetric membranes via a unique combination of phase inversion and sol-gel chemistry to overcome this big challenge. The SnO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The cyclic stability of A‐SnO 2 /rGO is much better than that of N–SnO 2 /rGO when the current density enhanced to 1 C (Figure d). After 300 cycles, the specific capacity of A‐SnO 2 /rGO was kept at 414.2 mAh g −1 , while the capacity of N‐SnO 2 /rGO was reduced to 150.6 mAh g −1 at 1 C. At the same time, the A‐SnO 2 /rGO electrode shows an outstanding Coulombic efficiency with an average Coulombic efficiency close to 100% in the cycles either at 0.1 C or 1 C implying its well electron and Li + ion transports …”
Section: Resultsmentioning
confidence: 97%
“…The cyclic stability of A‐SnO 2 /rGO is much better than that of N–SnO 2 /rGO when the current density enhanced to 1 C (Figure d). After 300 cycles, the specific capacity of A‐SnO 2 /rGO was kept at 414.2 mAh g −1 , while the capacity of N‐SnO 2 /rGO was reduced to 150.6 mAh g −1 at 1 C. At the same time, the A‐SnO 2 /rGO electrode shows an outstanding Coulombic efficiency with an average Coulombic efficiency close to 100% in the cycles either at 0.1 C or 1 C implying its well electron and Li + ion transports …”
Section: Resultsmentioning
confidence: 97%
“…The addition of carbon black is necessary to maintain the porous structure after being carbonized at high temperatures, and enhance the overall membrane conductivity. The formation mechanism of asymmetric membranes can be easily understood using a ternary phase diagram, which has been discussed explicitly in our previous studies . To describe it briefly, the homogeneous phase made of solvent (N‐methyl‐2‐pyrrolidone: NMP) and polymer (Polyacrylonitrile: PAN) is separated into two phases (polymer lean and polymer rich) after being immersed into non‐solvent (deionized water), due to the mixing of solvent and non‐solvent, and de‐mixing of polyacrylonitrile from the solvent/non‐solvent (NMP/water) mixture ,.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, tremendous effort has been made to explore the fundamental basics of high-capacity and high-energy electrode materials and many strategies have been proposed to conquer the obstacles of boosting energy density of the batteries. One strategy is to reduce particle size to nanoscale to alleviate mechanical strain. For example, Liu et al found that, during the first lithiation process, the nanoparticles with diameters less than 150 nm undergo volume expansion without fracturing or cracking, suggesting that nanoparticles can tolerate huge volume change .…”
Section: Corn-mediated Carbonaceous Host Matrixes For High-capacity E...mentioning
confidence: 99%